Utilization of Er:YAG Laser in Retrieving and Reusing of Lithium Disilicate and Zirconia Monolithic Crowns in Natural Teeth: An In Vitro Study - Kinga Grzech-Leśniak; Sompop Bencharit; Lenart Skrjanc; Domen Kanduti; Jacek Matys; Janina Golob Deeb (Applied Sciences, 2020)
The study examined the effect of noninvasive crown retrieval/reuse process using an erbium-doped yttrium aluminum garnet laser (Er:YAG). Twenty-six extracted human teeth were prepared for a crown. The crown was milled using lithium disilicate (LD) and zirconia (Z) materials, n = 13 per group, with three for scanning electron microscopy (SEM). The crown was luted using composite resin cement and subjected to a laser retrieval process. After the retrieval process, the crown was cleaned, re-cemented and laser-retrieved two more times, without and with additional tooth reduction mimicking clinical refreshment of dentin. Retrieval time and temperature were analyzed using analysis of variance (ANOVA). Surface changes were observed through SEM. The retrieval times were 267.1 ± 130.43, 220 ± 79.09, 277.1 ± 126.44, 368.4 ± 136.14, 355 ± 159.39, and 419.2 ± 121.36 s for first, second, third LD and Z groups, respectively (p = 0.009). The maximal temperatures were 23.95.1 ± 1.89 °C, 24.86 ± 2.01 °C, 24.17 ± 1.53 °C, 22.88 ± 1.51 °C, 24.03 ± 1.74 °C, and 21.99 ± 1.32 °C for first, second, third LD and Z groups, respectively (p = 0.006). Er:YAG laser crown removal is an effective retrieval tool for all-ceramic crowns. Minimal changes to teeth and crowns were observed following laser irradiation.